2021
DOI: 10.1097/md.0000000000028267
|View full text |Cite
|
Sign up to set email alerts
|

Muscle involvement with pseudohypertrophy in systemic light chain amyloidosis

Abstract: Rationale: Muscle pseudohypertrophy is a rare manifestation of light chain amyloidosis (AL) amyloidosis. Patient concerns: A 63-year-old woman presented with a 2-year history of progressive asthenia, macroglossia, dysphonia, cachexia, hypotension, paresthesia, and lower limb muscle hypertrophy. Diagnosis: Free serum lambda light chains were increased, and fat pad biopsy demonstrated Congo red-positive deposits. Additionally, electromyography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Muchtar et al [ 5 ] identified a few common features to skeletal muscle involvement in AL amyloidosis, in an observational study of a cohort of 51 patients: first, the strong association of amyloid myopathy with lambda light chain dysproteinemia; secondly, the muscle biopsy findings, characterized by rare necrotic and regenerating fibers and interstitial amyloid deposits in intramuscular blood vessels, which are consistent with previous reports [ 10 ]; lastly, the shared clinical aspects, such as proximal muscle weakness, dysphagia, macroglossia and, less frequently, muscular pseudohypertrophy or respiratory distress [ 5 , 11 , 12 ]. In addition, cardiac troponin T elevation, without evidence of cardiac involvement, might provide a clue enabling early diagnosis [ 2 , 5 ].…”
Section: Discussionsupporting
confidence: 86%
“…Muchtar et al [ 5 ] identified a few common features to skeletal muscle involvement in AL amyloidosis, in an observational study of a cohort of 51 patients: first, the strong association of amyloid myopathy with lambda light chain dysproteinemia; secondly, the muscle biopsy findings, characterized by rare necrotic and regenerating fibers and interstitial amyloid deposits in intramuscular blood vessels, which are consistent with previous reports [ 10 ]; lastly, the shared clinical aspects, such as proximal muscle weakness, dysphagia, macroglossia and, less frequently, muscular pseudohypertrophy or respiratory distress [ 5 , 11 , 12 ]. In addition, cardiac troponin T elevation, without evidence of cardiac involvement, might provide a clue enabling early diagnosis [ 2 , 5 ].…”
Section: Discussionsupporting
confidence: 86%
“…Every firm needs an analysis tool to assess market conditions and trends. In today's world, there is no survival in the industry without proper tools to function [4], [5].…”
Section: Predictive and Prescriptive Analyticsmentioning
confidence: 99%